Strengthening Non-military Defense to Strengthen the Unitary State of the Republic of Indonesia - Buana, I Gusti Putu (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study aims to explore effective strategies and measures necessary to strengthen non-military defence in Indonesia in response to increasingly complex non-military threats driven by technological advancements and globalisation. Design/Methodology/Approach: The research adopts a qualitative approach with descriptive analysis to investigate inter-agency coordination, community participation, and technological integration as key elements of non-military defence strategy. Data were collected from various sources, including relevant legislation, academic studies, and real cases in Indonesia. Findings: The analysis indicates that although Article 30(2) of the 1945 Constitution and Article 7(3) of Law No. 3 of 2002 emphasise the importance of participation by all national components, the implementation of non-military defence in Indonesia faces challenges due to unclear legal frameworks and insufficient inter-agency coordination. The 2023 cyber-attacks underscore the urgency for comprehensive regulation and effective coordination practices. Originality/Value: This study contributes new insights by proposing a multidimensional approach to reinforce non-military defence through cross-agency collaboration, enhanced digital capacity, and community involvement, aiming to build a more responsive defence system